2018
DOI: 10.1152/ajpendo.00362.2017
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training recovers attenuated APPL1 expression and improves insulin-induced Akt signal activation in skeletal muscle of type 2 diabetic rats

Abstract: Adapter protein containing Pleckstrin homology (PH) domain, phosphotyrosine-binding (PTB) domain, and leucine zipper motif 1 (APPL1) has been reported as a positive regulator of insulin-stimulated Akt activation. The expression of APPL1 is reduced in skeletal muscles of type 2 diabetic (T2D) animals, implying that APPL1 may be an important factor affecting insulin sensitivity. However, the regulation of APPL1 expression and the physiological interventions modulating these effects are unclear. Accordingly, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
(52 reference statements)
1
14
1
1
Order By: Relevance
“…Furthermore, RT used in this study has been reported to increase IGF‐1 protein expression, and improve glucose metabolism in muscle (Kido et al. ), which might indirectly enhance bone metabolism. From the above, we considered that RT has direct and indirect beneficial effects on improving BMD and bone structure in both cortical and trabecular bone of OLETF as well as LETO rats.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, RT used in this study has been reported to increase IGF‐1 protein expression, and improve glucose metabolism in muscle (Kido et al. ), which might indirectly enhance bone metabolism. From the above, we considered that RT has direct and indirect beneficial effects on improving BMD and bone structure in both cortical and trabecular bone of OLETF as well as LETO rats.…”
Section: Discussionmentioning
confidence: 92%
“…; Kido et al. ). Briefly, under isoflurane anesthesia, the whole right gastrocnemius muscle (RT leg) was subjected to maximal isometric contraction by percutaneous electrical stimulation (5 sets of 3‐sec stimulations × 10 contractions/set with a 7‐sec interval between contractions and a 3‐min rest between sets) with an electric stimulator and isolator (SS‐104J; Nihon Kohden, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations